2016
DOI: 10.5535/arm.2016.40.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Supraorbital Sensory Nerve Conduction Recordings: Orthodromic and Antidromic Techniques

Abstract: ObjectiveTo establish a supraorbital nerve sensory conduction recording method and assess its usefulness.MethodsThirty-one healthy subjects without a history of trauma or neurological disease were recruited. For the orthodromic procedure, the recording electrode was attached immediately superior to the supraorbital notch. The stimulation electrode was placed on points along the hairline which evoked the largest sensory nerve action potentials (SNAPs). The antidromic sensory response was recorded after switchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
2
2
Order By: Relevance
“…However, the intra‐side and inter‐side differences in amplitude were not significantly different. The reference SNAP amplitudes of the STN and SONs obtained in our study were significantly higher than those reported by Park because our normal amplitude values used near‐nerve techniques, which show greater responses.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…However, the intra‐side and inter‐side differences in amplitude were not significantly different. The reference SNAP amplitudes of the STN and SONs obtained in our study were significantly higher than those reported by Park because our normal amplitude values used near‐nerve techniques, which show greater responses.…”
Section: Discussioncontrasting
confidence: 83%
“…However, the intra-side and inter-side differences in amplitude were not significantly different. The reference SNAP amplitudes of the STN and SONs obtained in our study were significantly higher than those reported by Park 25 distal latencies, which are reported to vary with age. 34 Statistically significant differences in any of the parameters analyzed in this study were not observed between groups stratified by gender and age, and part of the reason may be that the age groups of the recruited subjects were relatively narrow.…”
Section: Snaps Of the Sons And Stncontrasting
confidence: 82%
See 2 more Smart Citations